BASE MODELS IN COMPUTER-BASED PEDAGOGICAL DIAGNOSTICS SYSTEM - O. Kolgatin (Kherson State University, 2012)
The structure of base models in a computer-based pedagogical diagnostics system is proved: the learning objectives model, the psychological and pedagogical model of student, the model of learning technology realisation. The structure of corresponding data bases of information system is suggested.